Anti-fungal activity of SiO(2)/Ag(2)S nanocomposites against Aspergillus niger - Fateixa, Sara (2009)
Submicron particles of amorphous SiO2 have been used to grow Ag2S nanophases at their surfaces. SEM and TEM analysis showed morphological well-defined nanocomposite particles consisting of Ag2S nanocrystals dispersed over the silica surfaces. These SiO2/Ag2S nanocomposites were investigated as anti-fungal agents against Aspergillus niger in different experimental conditions, including as nanofillers in cellulosic fibres. The anti-fungal activity in these composite systems is suggested to result from a synergistic effect due to Ag2S anti-fungal centres and the SiO2 surfaces in promoting the adsorption of the fungus.